Assessment of a flipped-classroom approach to teach deprescribing and safe medication use in a geriatric pharmacotherapy module - Clark, Collin; Maerten-Rivera, Jaime; Prescott, William; Doloresco, Fred; Wahler, Robert (Pharmacy Education, 2023)
Objective: To assess the impact of a flipped-classroom approach to teach safe medication use and deprescribing for older adults on student academic performance and perceptions of deprescribing. Methods: This was a pre-post evaluation following implementation of the flipped-classroom approach in a third-year pharmacotherapy course. The primary endpoint was the difference in exam performance on 10 related assessment items. An electronic survey was distributed to students in both cohorts to assess their attitudes, perceived ability, and confidence in deprescribing (5-point Likert-scale). Results: The average score on covered exam items was 74.6% in the lecture group and 75.6% in the flipped-classroom group (p = 0.62). Students in the flipped-classroom group were more likely to endorse confidence in their ability to recommend appropriate deprescribing strategies for potentially inappropriate medications (p = 0.02). Conclusions: Learners reported increased self-confidence with deprescribing in practice when taught using the flipped-classroom approach, but exam scores were not significantly improved.